In vitro cytotoxicity of superheated steam hydrolyzed oligo((R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate) and characteristics of its blend with poly(L-lactic acid) for biomaterial applications. - Dhurga Devi Rajaratanam; Hidayah Ariffin; Mohd Ali Hassan; Nik Mohd Afizan Nik Abd Rahman; Haruo Nishida (PLoS ONE)
In order to clarify the in vitro cytotoxicity effect of superheated steam (SHS) treated poly((R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate) (PHBHHx) for biomaterial applications, SHS-treated PHBHHx oligoester samples: P(HB-co-6%-HHx) and P(HB-co-11%-HHx) with low and high percentages of unsaturated chain ends were evaluated for their cytotoxicity effects toward the growth of mouse fibroblast cell line NIH 3T3. From the results obtained after 24 and 48 h of the growth test, the SHS-treated PHBHHx oligoesters were found to be nontoxic to the growth of mouse fibroblast NIH 3T3 cell line with cell viability percentages of more than 95%. In order to serve as a potential resorbable medical suture, PHBHHx oligoesters were blended with poly(L-lactic acid) (PLLA) with a weight ratio of PHBHHx oligoester/PLLA = 20:80 (wt/wt) to improve mechanical properties of PHBHHx oligoesters. The PHBHHx oligoesters/PLLA blend films were evaluated for their thermal, mechanical, and surface wetting properties. Thermal properties of the blend films suggested a good compatibility between PHBHHx oligoesters and PLLA components. Mechanical properties of the blend films were determined to be close enough to a desirable strength range of medical sutures. Moreover, contact angle range of 65 < θ < 70° for the blend samples could provide desirable cell adhesion when used as biomaterials. Therefore, the blend of SHS-treated PHBHHx oligoesters and PLLA would be an ideal choice to be used as biomedical materials.